Performance of Eight Methods, Including Two New Rapid Methods, for Detection of Oxacillin Resistance in a Challenge Set of Staphylococcus aureus Organisms - Swenson, Jana M. (American Society for Microbiology, 2001)
Using a set of 55 Staphylococcus aureus challenge organisms, we evaluated six routine methods (broth microdilution, disk diffusion, oxacillin agar screen, MicroScan conventional panels, MicroScan rapid panels, and Vitek cards) currently used in many clinical laboratories and two new rapid methods, Velogene and the MRSA-Screen, that require less than a day to determine the susceptibility of S. aureus to oxacillin. The methods were evaluated by using the presence of the mecA gene, as detected by PCR, as the “gold standard.” The strains included 19 mecA-positive heterogeneously resistant strains of expression class 1 or 2 (demonstrating oxacillin MICs of 4 to >16 μg/ml) and 36 mecA-negative strains. The oxacillin MICs of the latter strains were 0.25 to 4 μg/ml when tested by broth microdilution with 2% NaCl-supplemented cation-adjusted Mueller-Hinton broth as specified by the NCCLS. However, when tested by agar dilution with 4% salt (the conditions used in the oxacillin agar screen method), the oxacillin MICs of 16 of the mecA-negative strains increased to 4 to 8 μg/ml. On initial testing, the percentages of correct results (% sensitivity/% specificity) were as follows: broth microdilution, 100/100; Velogene, 100/100; Vitek, 95/97; oxacillin agar screen, 90/92; disk diffusion, 100/89; MicroScan rapid panels, 90/86; MRSA-Screen, 90/100; and MicroScan conventional, 74/97. The MRSA-Screen sensitivity improved to 100% if agglutination reactions were read at 15 min. Repeat testing improved the performance of some but not all of the systems.